Analysis of Service Quality on Customer Satisfaction with Gap-Servqual Method and Importance Performance Analysis - Santoso, Cindi Adelia; Riyanto, Dicky Wisnu Usdek; Nurjannah, Dewi (Business Innovation Management and Entrepreneurship Journal, 2024)
In this digital era, understanding and meeting customer satisfaction is crucial with the increasing number of choices and customer expectations. This study aims to determine the quality of service and satisfaction at Klinik X Kota Malang. The samples in this study were 145. The sampling technique used was accidental sampling. The type of research used is survey explanatory with a quantitative approach. The data collection technique used was a questionnaire. Data analysis used the Service Quality Method (SERVQUAL) and Importance Performance Analysis (IPA). The results of this study show that the quality of services provided by Klinik X Kota Malang has not fully met consumer expectations, and the satisfaction achieved by customers cannot be fully felt with the quality of services provided by the company. The study highlights that service quality is important in determining customer satisfaction, so the company needs to improve the quality of service identified as not optimal.